Preservice Special Education Teachers' Use of Behavior‐Specific Praise: Effects on Middle School Students With Moderate Intellectual Disabilities - Çakıroğlu, Orhan (Behavioral interventions, 2025)
ABSTRACT Behavior‐specific praise (BSP) is an evidence‐based strategy that reinforces appropriate student behavior and improves classroom engagement, yet its implementation remains inconsistent among preservice special education teachers. This study examines the effects of BSP training on the instructional practices of preservice special education teachers and the on‐task behavior of middle school students with moderate intellectual disabilities. This study employed a single‐subject multiple‐baseline design, wherein three preservice teachers received structured training, real‐time coaching, and performance feedback to enhance BSP implementation. Results showed increased BSP implementation among preservice teachers, highlighting the need for ongoing support to sustain these practices.